A pXRF‐based geochemical dataset of typical boreholes in Xuancheng Qiaomaishan copper–sulphur deposit - Mingming Zhang; Junqin Jiao; Guoyu Zhou; Siyang Li; Chengbao Wang; Jinxiao Long; Can Ge; Liang Wang; Hongdong Fang (Geoscience Data Journal, 2024)
Abstract Drilled cores provide first‐hand data for deposit research. The element compositions at different depths of cores are an important basis for evaluating the reserves of mineral deposits. Therefore, a dataset containing a complete drill core element content has great value on practicality. In this study, a pXRF analyser was used to measure the element contents in eight cores of the Xuancheng Qiaomaishan copper–sulphur deposit ZK16 + 02, ZK16 + 03, ZK16 + 04, ZK1804, ZK18 + 02, ZK1403, ZK1602, and ZK1604, and a geochemical dataset was obtained. The dataset includes Cu, S, Fe, W, Mg, Al, Si, As, Mn, Co, Ni, Zn, Se, Ti, V, Cr, Ca, Cl, P, Sr, Y, Zr, Nb, Mo, Pb, Th, U, and other 27 major and trace elements. Based on this dataset, the vertical variation pattern of main and trace element content in drill cores can be examined, the distributions of elements in full hole or exploration line profile can be drawn, and element correlation analysis and principal component analysis can be performed.